Examining Factors Affecting the Accountability of the Performance of Regional Apparatus Organizations - Dyah Poespita Ernawati (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
The purpose of this study was to obtain empirical evidence of the influence of competence, leadership style, organizational culture, use of technology, and reporting systems on the performance accountability of government agencies in OPD Sumedang Regency. This research approach uses a scientific method which is a theoretical structure to form a hypothesis. It then uses facts or empirical data to test the theory to conclude or be conclusive. The data collection technique in this study used a questionnaire distributed directly to the OPD of the Sumedang Regency. The population in this study were all OPD Sumedang Regency, as many as 31 OPD. Sampling in this study using the purposive sampling technique. Respondents in this study were the head of financial administration and administrative staff. So, the total sample of this research is 31 x 2 apparatus = 62 OPD apparatus in Sumedang Regency. Data processing technique using SEM method based on Partial Least Square (PLS). The study results found that competence, leadership style, organizational culture, and technology had a positive and significant effect on the accountability of government agencies' performance at OPD Sumedang Regency. At the same time, the reporting system has a positive but not significant impact on the Performance Accountability of Government Agencies at OPD Sumedang Regency.